EXPLORING TEACHERS’ BELIEFS AND PRACTICES OF PEDAGOGICAL COMPETENCIES IN TEACHING ENGLISH TO YOUNG LEARNERS - Desi Astuti; Endang Fauziati; Sri Marmanto (Universitas Muhammadiyah Semarang, 2019)
Having pedagogical competencies is one of the requirements to become a professional teacher in Indonesia. That is to say, teachers must master this competence and English teachers of young learners are not exempt. Thus, this study was conducted in order to explore the English teachers’ beliefs on pedagogical competencies in teaching English to young learners and how their beliefs were reflected in the teaching-learning process. Interviews and observations have been conducted to collect qualitative data from the participants in Surakarta. Included in this study were 2 English teachers at a private school in Surakarta. The results of the study indicated that the English teachers faced several challenges in implementing their beliefs on pedagogical competencies. The study we have done suggests that pedagogical competencies of the English teachers can be developed through a professional development program which should be organized by every school in Indonesia.